PENYULUHAN PENCEGAHAN PENYAKIT DIARE DENGAN MENJAGA KEBERSIHAN LINGKUNGAN PESISIR DI DESA DAEO MAJIKO KECAMATAN MOROTAI SELATAN - Cabu, Roberto; Mofu, Johan Gaspel; Lahura, Yulianti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2025)
The purpose of implementing health counseling in the village of Daeo Majiko is to provide education to the public about the dangers of diarrhea and how to prevent it, increase awareness of the importance of the cleanliness of the coastal environment, and foster clean and healthy life behavior in coastal communities. The implementation of community service activities is carried out systematically through three main stages, namely the stages of preparation, implementation of counseling, and evaluation of activities. The results of the evaluation of the activity showed that the participants had increased knowledge about diarrhea, the cause of diarrhea and how to prevent and overcome them, so that this community extension activity can be said to benefit the community.